Metacognition and Middle Grade Mathematics Teachers: Supporting Productive Struggle. Issue 1 (4th March 2019) - Lemley, Stephanie M.; Ivy, Jessica T.; Franz, Dana Pomykal; Oppenheimer, Seth F.
Abstract: Communicating mathematical ideas through writing, listening, and verbalizing allows students to think about how they "think" about mathematics. By focusing this communication on a reflection of how one thinks about mathematics, metacognitive writing engages students as mathematicians and learners. In this article we describe a professional development that we implemented with middle grade mathematics teachers focused on metacognitive writing as a tool to support productive struggle in the mathematics classroom. Thus, this practitioner article adds to the knowledge base on how to develop middle grade teachers metacognitive writing through engagement in productive struggle. Recommendations for practice are included.